Sistem Informasi Analisis dan Evaluasi Kepuasan Pengunjung Berbasis Web: Studi Kasus: Tempat Wisata Pantai Kibito Amona Nabire - Usman Arfan; Margaretha Y. Douw (Jurnal Teknologi dan Informatika, 2024)
This research develops a web-based information system for analyzing and evaluating visitor satisfaction at Kibito Amona Nabire Beach. The system collects automated data from online surveys, visitor reviews, and social media, which it analyzes to identify satisfaction patterns and trends. Using prototype methodology, the system was designed, developed, and tested to ensure accuracy and efficiency. The technology used includes MySQL for the database and Macromedia Dreamweaver for interface design. The results are expected to improve visitor satisfaction management, even though there are limitations such as limited access only to the beach area and site management by one admin.